Application of Random Forest Method Classification to Predict BPJS Kesehatan Card Users Who Receive Contribution Assistance in Karangasem District, Bali Province 2017 - Raihananda, Qonita; Putra, I Wayan Edy Darma; Sijabat, Monica Seftaviani; Rofatunnisa, Sifa; Maruf, Ibnu; Hermarwan, Hermarwan; Nooraeni, Rani (Jurnal Matematika, Statistika dan Komputasi, 2020)
BPJS Kesehatan is a social security facility provided by the government to all people who are registered as members. BPJS Kesehatan membership is divided into two, namely BPJS for Contribution Assistance Recipients (BPJS PBI) and BPJS Non-Contribution Assistance Recipients (BPJS Non-PBI). In 2019, Bali Province is targeted to achieve Universal Health Coverage of 95 percent so that the Bali Provincial Government has budgeted funds worth IDR 945 billion to finance JKN - KBS services which are integrated with JKN - KIS. Karangasem is one of the four districts in Bali Province that received the most percentage of financing, which is 51 percent of the total budget needed when compared to other areas. This study aims to classify the BPJS-PBI recipient community based on education variables, employment indicators, age, and per capita expenditure in Karangasem Regency in 2017. The classification method used in this study is the random forest method. The results showed that the per capita expenditure variable had the largest contribution in classifying the status of PBI participants. The model that is formed produces an accuracy of 0.8017. This means that the model can predict 80.17 percent testing data correctly.